Critical Theory for Library and Information Science - Leckie, Gloria J. (Libraries Unlimited, 2012)
Critical theory is present but relatively underdeveloped in the field of library and information science. The success of scholarly learning and information science as a whole depends on library specialists who understand the value of applying critical theoretical perspectives to real-world challenges.